Causal relationship between gut microbiota and immune thrombocytopenia: a Mendelian randomization study of two samples - Guo, Dongmei; Chen, Qian; Wang, Guojun; Li, ChunPu; , FinnGen consortium (Frontiers in Microbiology, 2023)
Background: Some observational studies have illustrated that immune thrombocytopenia (ITP) is tightly associated with the alteration-composition of gut microbiota. Nevertheless, the causality of gut microbiota on ITP has not yet been determined.Based upon accessible summary statistics of the genome-wide union, the latent connection between ITP and gut microbiota was estimated using bi-directional Mendelian randomization (MR) and multivariable MR (MVMR) analyses. Inverse variance weighted (IVW), weighted median analyses, and MR-Egger regression methods were performed to examine the causal correlation between ITP and the gut microbiota. Several sensitivity analyses verified the MR results. The strength of causal relationships was evaluated using the MR Steiger test. MVMR analysis was undertaken to test the independent causal effect. The MR analyses of reverse direction were made to exclude the potential of reverse correlations. After all, GO enrichment analyses were carried out to explore the biological functions.Results: After FDR adjustment, two microbial taxa were identified to be causally associated with ITP (PFDR < 0.10), namely Alcaligenaceae (PFDR = 7.31× 10 -2 ) and Methanobacteriaceae (PFDR = 7.31× 10 -2 ). In addition, eight microbial taxa were considered as potentially causal features under the nominal significance (P < 0.05), including Actinobacteria, Lachnospiraceae, Methanobacteria, Bacillales, Methanobacteriales, Coprococcus2, Gordonibacter, and Veillonella. According to the reverse-direction MR study findings, the gut microbiota was not significantly affected by ITP. There was no discernible horizontal pleiotropy or instrument heterogeneity. Finally, GO enrichment analyses showed how the identified microbial taxa participate in ITP through their underlying biological mechanism.Conclusions: Several microbial taxa were discovered to be causally linked to ITP in this MR investigation. The findings improve our comprehension of gut microbiome on the risk of ITP.